Proposal to improve the solids and grease recovery process from pumping water at Copeinca Chancay 2022 (SCIÉNDO INGENIUM, 2026)
The central proposal of this was to improve the efficiency of grease traps by incorporating a pressurized system with compressed air to the solids and grease recovery traps, projecting to increase the recovery of total suspended solids from 13,47% in (TSS) and 29,15% fats (ppm) by 60% in both TSS and grease (ppm) The problem is caused by the water being pumped out of the flotation cells, which averages 11794 ppm in total suspended solids, 6225 ppm in grease, and has a pH of 6,44. The high fat content makes treatment difficult in the chemical stage to meet the maximum permissible limits of 700 ppm TSS, 350 ppm fat and pH between 5,0 – 9,0. The design parameter values ​​were calculated as 0,011 ml air/mg solids and 0,017 ml air/mg fat at a recirculation flow rate of 300 m3/h. Using Henry's law and the Setschenow coefficient, the solubility of air in seawater was calculated as 3,67×10−3 mol/L with an air flow rate of 31,8 kg/h.The economic analysis shows that the proposal is profitable, with an IRR of 179%, NPV of $656845,33 and a payback of 0,58 years.
Keywords: Pumping water; Total suspended solids (TSS) and grease; solubility; dissolved air flotation (DAF); grease traps and recovery efficiency